El principio de intangibilidad de los Derechos de los Trabajadores, y el sustento a las garantías a las indemnizaciones pormenorizadas en la terminación de la relación laboral por acuerdo mutuo - Jirón Tandazo, Galo Manuel (2016)
Rights at work in labor - management relations constitute the core of the productive and economic system of a society, so the work is considered as a key point in the development of large companies or public or private institutions run by entities economic and the state or employers. The labor law does not stipulate a time term for the payment of workers' compensation settlement or the termination of the contractual relationship, which provides that the employer must pay the employee wages and benefits due to termination of the employment contract, under penalty of having to pay compensation to the same standard states as punishment for nonpayment appropriate. Furthermore, the jurisprudence of the Supreme Court in repeated failures related to the payment of labor settlements, has established that compensation for its object, and not depend upon timely cancellation there are no reasons justifying the delay by the employer, which to go to the right through a labor demand for compensation for such payment, the order is imperative, therefore canceling the worker is compulsory for your employer and should be in detail to the legal effect. Consequently, compensation for time must be based on the basis of the remuneration received by the employee during the provision of their services, and all those amounts which are benefits to workers, it must be determined that when there is mutual agreement between the parties, this agreement is subject to that stipulated in detail the items to which the employee is entitled, and cover each making up a compensation for the termination of the contractual relationship.